Tinjauan Hukum Islam Tentang Mekanisme Akad Menggunakan E-WALET Pada Aplikasi GO-PAY - Izzan, Ahmad; Haris, Ajang Ahmad (STAI Al Musaddadiyah Garut, 2023)
Go-Pay is electronic money that can be used to conduct financial transactions through the G0-Jek application. Go-Pay is almost similar to a credit card, over time, transactions through Go-Pay can not only apply to transactions in the Go-Jek application feature. Currently, transactions through Go-Pay as well as information on Go-Jek can be done at Go-Pay's business partners.Related to this, there are different views in the perspective of Islamic Law regarding halal or haram using the service. The formulation of the problem is: How is the transaction practice on the contract system used in the Go-Pay application, How is the Review of Islamic Law About the mechanism of the contract using e-wallets in the Go-Pay application. The purpose is to find out the perspective of Islamic law on the mechanism of the contract using e-wallet on the Go-Pay application. This research is a literature research (Library Research) where data and data sources are obtained from a review of literature that is in accordance with the problem. The method used is descriptive analytical, technical data analysis used in the form of qualitative data analysis. Based on the results of the study, E-wallet is a type of electronic card used for transactions, the mechanism of transaction contracts through Go-Pay services is included in the type of Mujtami'ah Hybrid contract, which is multi contracts (a combination of several contracts) collected in one contract. The transaction agreement using this E-wallet has fulfilled the pillars and requirements in the type of buying and selling (order).